The Influence of Emotional Intelligence on the Professionalism of SMKN Teachers in Bandar Lampung City - Poniman, Poniman; Suryanadi, Juni; Ardianto, Hendri (Journal of Adaptive Education, 2023)
This study aimed to explore, study and analyze the influence of teacher emotional intelligence on teacher professionalism at SMK Negeri Bandar Lampung. This research is quantitative research using the ex post facto method, the data collection technique is a questionnaire through five answer choices and initial testing of research tools, including validity and reliability tests. Hypothesis testing is done using simple linear regression analysis. The total population of this study was 695 teachers, with the sampling technique using the Taro Yamane formula and a sample of 237 teachers was obtained. The study results, in general, indicate a positive and significant influence of emotional intelligence on teacher professionalism.